The General and Systemic Consequences of Obesity in Cats and Dogs - Wajahat Masood (Veterinary Integrative Sciences, 2024)
Obesity, is a life-threatening condition common among various animals, is a multisystemic disorder that may affect the gastrointestinal system, urinary system, reproductive system, respiratory system, and musculoskeletal system. According to various studies, more than 50% of cats and dogs are obese. Many proinflammatory and inflammatory cytokines, hormones, and enzymes play a part in the production of fat tissues that lead to obesity. Excessive deposition of fats give rise to conditions involving inflammation, oxidative stress and damage, immunomodulation, hyperlipidemia, dyslipidemia, neoplasia, hypothyroidism, and insulin resistance. This review paper acquires the knowledge of various scientific manuscripts to discuss the development and consequences of obesity in pets especially cats and dogs.